Thermally stimulated transformations in thin films of cryovacuum condensates of methane - Drobyshev, A.; Aldiyarov, A.; Nurekeyev, Zh.; Tychengulova, A. (Recent Contributions to Physics, 2015)
Solid methane belongs to a group of crystals which contains molecules of hydrogen, whose macroscopic properties (thermal expansion, etc.) are greatly caused by spin interaction of nucleus of hydrogen. In particular, the methane molecule, which has four protons with spin I = 1/2, has three total spin modifications: para-, ortho- and meta- states with three values of the total spin moments of 0, 1 and 2, accordingly.